HUBUNGAN ANTARA STATUS GIZI DENGAN USIA MENARCHE PADA REMAJA PUTRI DI DESA BRAJAN MOJOSONGO BOYOLALI - Sri Aminingsih; Kharisma Ayu Susilowati; Ichlasi Lintang Suminar (KOSALA : Jurnal Ilmu Kesehatan, 2015)
AbstractIntroduction: Based on the results of a survey conducted on 3 while young women who have not experienced menarche at Brajan village district ofMojosongo Boyolali, one of which weighed 34 kg and height 130 cm so that her BMI 20.12 included in the normal BMI classification, while one young woman has severe weight 25 kg and height 120 cm so that her BMI 17.36, and 1 teenage daughter weighing 34 kg and height 137 cm so that her BMI 18.08. Both BMI calculation results of these two young women were categorized as underweight light.The Purpose: To determine the relationship between nutritional status and age of menarche in young women in the Brajan village district of Mojosongo Boyolali.Method: Cross-sectional study.Subjects: The research subjects are 21 girls who are experiencing menarche10-14 years old. The study was conducted by assessing the results of the IMT. Data were analyzed with Chi Square test.The Results: Average rate age of menarche occurred at the age of 12.5 years and had normal nutritional status. Results chi squere p = 0.653 which means that p> 0.05.Conclusion: There is no relationship between nutritional status and age of menarche in adolescent girls at Brajan village district of Mojosongo Boyolali.Keywords: menarche, adolescent girls and nutritional status